Effectiveness of Relaxation Handheld Fingertechnique and Benson Relaxation to the Changes Level of Post Operative Pain Sectio Caesarea in Rsi Sakinah Mojokerto (International Journal of Scientific Research and Management (IJSRM), 2017)
Pain after major or minor surgery will impact the anatomical and physiological changes in patients. Giving anesthetic is not always sufficient to eliminate the sensation of pain because the pain response of each patient is different. Postoperative pain caesarea section must be solved with non-pharmacological methods of handheld eg relaxation techniques and relaxation benson finger. The purpose of this research was to prove efektikitas between both these relaxation techniques to changes in the level of postoperative pain section caesarea in RSI Sakinah Mojokerto. The researh design is pre experiment with methods of the two groups without pretest-posttest control group. The population in the researh of 20 respondents with nonprobability sampling technique that was concecutive sampling, while the samples are 10 respondents in the relaxation group and 10 respondents handheld finger on relaksai group benson. Analysis of data using univariate analysis showed a decrease in pain level respondents in the relaxation group handheld finger 10 respondents (100%), while the decrease in the level of pain in the relaxation group benson much as 8 respondents (80%). Wilcoxon statistical test results showed ρ = 0.005 <α = 0.05, for relaxation handheld fingers and ρ = 0.016 <α = 0.05 for benson relaxation, so H0 was rejected it means there was the influence of both good therapy relaxation techniques handheld fingers or relaxation benson but when compared fingers handheld relaxation techniques more effectively to changes in the level of postoperative pain caesarea section. The results of this reseach recommended relaxation techniques and relaxation benson finger handheld can be used as a standalone action undertaken nonpharmacologic nursing nurses to reduce the level of postoperative pain caesarea section.